Aging-associated sensory decline and Alzheimer’s disease - Suji Hong; Seung-Hyun Baek; Mitchell K. P. Lai; Thiruma V. Arumugam; Dong-Gyu Jo (Molecular Neurodegeneration)
Abstract Multisensory decline is common as people age, and aging is the primary risk of Alzheimer’s Disease (AD). Recent studies have begun to shed light on the possibility that age-related sensory decline could accelerate AD pathogenesis, or be a prodromal indicator of AD. Sensory impairments, specifically in taste and smell, often emerge before cognitive symptoms in AD, indicating their potential as early biomarkers. Olfactory dysfunction has been frequently associated with AD and may offer valuable insights into early detection. Hearing impairment is significantly associated with AD, but its causal impact on AD progression remains unclear. The review also discusses visual and tactile deficits in AD, including retinal thinning and changes in tactile perception, highlighting their links to disease progression. Focusing on molecular mechanisms, the review explores the roles of amyloid-β (Aβ) accumulation and tau protein pathology in sensory decline and their bidirectional relationship with AD. In summary, the evidence presented conclusively supports advocating for an integrated approach to understanding AD and sensory decline, to enhance early detection, implementing preventive strategies, and developing therapeutic interventions for AD. This approach underscores the significance of sensory health in addressing neurodegenerative diseases, particularly AD.